Characteristics and Ideotype Formulation of Pulasan (Nephelium ramboutan-ake) Fruit Landrace from West Java, Indonesia - Djuita, Nina Ratna; Hartana, Alex; Chikmawati, Tatik; Dorly, (Makara Journal of Science, 2019)
Pulasan (Nephelium ramboutan-ake) is a unique tropical fruit, but its morphological variations have not been well characterized. This study was conducted to obtain data on the characteristics of pulasan landrace in West Java, Indonesia, and to formulate the ideotype of pulasan with superior characteristics, such as high fruit weight, sweet taste, and thick and easily peelable aril from the seed. Based on the descriptors of rambutan, 61 fruit variants were observed. The results showed that the average fruit weight was 46.0 g, with the highest at 103.5 g and the lowest at 23.1 g. The °Brix level variation of pulasan fruit was 16.8–29.6, and its vitamin C content was 14.0–24.0 mg/100 g. Five variants with superior fruit characters were identified among the sample collections used in the study